(untitled) (The Review of Diabetic Studies, 2025)
Emergency departments (EDs) operate under high-pressure conditions where rapid decision-making, effective communication, and coordinated care are vital to patient outcomes. The complexity of cases presenting in EDs often requires input from multiple healthcare professionals, making the role of multidisciplinary health teams (MDTs) critical. This review explores the contribution of MDTs—including physicians, nurses, pharmacists, paramedics, social workers, and allied health staff—in enhancing the quality of patient care in emergency settings. Evidence from clinical and observational studies indicates that well-structured multidisciplinary collaboration reduces medical errors, shortens waiting times, improves diagnostic accuracy, and increases patient satisfaction. Furthermore, effective teamwork strengthens triage processes, optimizes resource utilization, and supports integrated patient-centered care. Despite these advantages, challenges such as communication barriers, hierarchical structures, and inconsistent protocols may limit team effectiveness. The review emphasizes strategies to strengthen MDT functioning, including interprofessional training, standardized communication models, and supportive institutional policies. By synthesizing current literature, this article underscores the transformative role of multidisciplinary health teams in improving both clinical outcomes and system performance in EDs. The findings highlight the need for continued investment in collaborative frameworks to ensure sustainable improvements in emergency care delivery.